Coping Mechanisms Used by Underprivileged Children in Addis Ketema, Addis Ababa - Bizuneh, Debebe (Daystar University, School of Applied Human Sciences, 2007)
This thesis explored the experiences of resilient children who were caring and supporting younger siblings following devastation in a family structure. Thirty four participants aged 17-20 years provided the data. These are young people whose stressful life situation started at least 6 year prior to this research, and who had at least two dependent younger siblings living in their home. The death of parent or being bedridden are among life's most difficult and stressful events to children. Child- headed families have become a common phenomenon in Sub-Saharan Africa partly due to the HIV and AIDS scourge. Guided conversation/dialogue was the primary source of data collection. Data analysis involved the use of the grounded theory approach. Findings showed the year after the stressful situation was the most difficult year of coping, implying the need for greater support during that year. Moreover, the results revealed a remarkable transformation, after at least three years of struggle, moving toward recovery. The study shows that those that provide care and counselling of underprivileged children should encourage them to examine and accomplish new goals that would enhance self-efficacy and quality of life in their roles as heads of families.
Master's Thesis
Keywords: resilient children